Endothelium‐derived dopamine modulates EFS‐induced contractions of human umbilical vessels. Issue 4 (22nd June 2020) - Britto‐Júnior, José; Pinheiro, David H. A.; Justo, Alberto F. O.; Figueiredo Murari, Guilherme M.; Campos, Rafael; Mariano, Fernanda V.; de Souza, Valéria B.; Schenka, André A.; Mónica, Fabiola Z.; Antunes, Edson; De Nucci, Gilberto
Abstract: Electrical field stimulation (EFS) induces contractions of both snake aorta and human umbilical cord vessels (HUCV) which were dependent on the presence of the endothelium. This study aimed to establish the nature of the mediator(s) responsible for EFS‐induced contractions in HUCV. Rings with or without endothelium from human umbilical artery (HUA) or vein (HUV) were mounted in organ bath chambers containing oxygenated, heated Krebs‐Henseleit's solution. Basal release of dopamine (DA), noradrenaline, and adrenaline was measured by LC‐MS‐MS. Cumulative concentration‐response curves were performed with dopamine in the absence and in the presence of L‐NAME or of dopamine antagonists. EFS studies were performed in the presence and absence of L‐NAME, the α‐adrenergic blockers prazosin and idazoxan, and the dopamine antagonists SCH‐23390 and haloperidol. Tyrosine hydroxylase (TH) and dopa‐decarboxylase (DDC) were studied by immunohistochemistry and fluorescence in situ hybridizations. Basal release of dopamine requires an intact endothelium in both HUA and HUV. TH and DDC are present only in the endothelium of both HUA and HUV as determined by immunohistochemistry. Dopamine induced contractions in HUA only in the presence of L‐NAME. Dopamine‐induced contractions in HUV were strongly potentiated by L‐NAME. The EFS‐induced contractions in both HUA and HUV were potentiated by L‐NAME and inhibited by the D2‐like receptor antagonist haloperidol. The α‐adrenergic antagonists prazosin and idazoxan and the D1‐like receptor antagonist SCH‐23390 had no effect on the EFS‐induced contractions of HUA and HUV. Endothelium‐derived dopamine is a major modulator of HUCV reactivity in vitro .